NATIONAL WORLDVIEW IN BILINGUAL COMMUNICATION - V. A. Iovenko (Vestnik MGIMO-Universiteta)
This article analyses the concept “national and cultural worldview” in the size of bilingual communication, examines peculiarities in mass media texts translation. The article establishes important types of divergences between Spanish and Russian worldviews which are relevant for translation, for example: abundance in Spanish mass media texts of specific and exotic national idiomatic units, bright stylistic locutions, figurative expressions, syntactic constructions, text structures which, when used in oral and written speech sound weird and unexpected for Russian native speakers. Spaniards often use words from different spheres of life (sports, medicine, warfare, etc) in political communicative situations. The research finds that the Spanish language tends to actively coin new words and combination patterns of “event” semantics. The article gives examples from Spanish-Russian translations and proposes ways to overcome divergences in the context of the Spanish worldview. The author makes conclusion that the national and cultural distinctions are the fourth reason, besides systems, norms and uses, of differences between languages.